2022
DOI: 10.1002/osp4.631
|View full text |Cite
|
Sign up to set email alerts
|

Perceived intrinsic, social, and environmental barriers for weight management in older Hispanic/Latino adults with obesity

Abstract: Background The burden of obesity and chronic disease is increasing in the older US Hispanic/Latino adult population. There is limited evidence on successful weight management strategies as perceived by this population. Assessing barriers and opportunities for weight management using mixed methods is a robust approach to collect in‐depth information that can be applied to the development of well‐tailored weight management interventions for this population. Objective The objective of this study was to assess per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…A recent systematic review exploring factors that are associated with SB in adults living with obesity, identified only 12 studies with few and weak associations, found no evidence for a consistent association and found no qualitative studies examining SB associations in this population. 14 Furthermore, while qualitative studies have focused on perceived determinants of weight loss, 15 obesity management, 16 physical activity, 17 healthy lifestyle or nutrition 18 in adults with obesity or adolescents, 19 few use a theoretical framework from study design through analysis. 20,21 Evidence for the effectiveness of SB interventions is also mixed or lacking, particularly outside the workplace, 22 and although some non-workplace interventions show promise, few target adults with obesity or explicitly report theoretical constructs 23 which would enhance replicability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review exploring factors that are associated with SB in adults living with obesity, identified only 12 studies with few and weak associations, found no evidence for a consistent association and found no qualitative studies examining SB associations in this population. 14 Furthermore, while qualitative studies have focused on perceived determinants of weight loss, 15 obesity management, 16 physical activity, 17 healthy lifestyle or nutrition 18 in adults with obesity or adolescents, 19 few use a theoretical framework from study design through analysis. 20,21 Evidence for the effectiveness of SB interventions is also mixed or lacking, particularly outside the workplace, 22 and although some non-workplace interventions show promise, few target adults with obesity or explicitly report theoretical constructs 23 which would enhance replicability.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review exploring factors that are associated with SB in adults living with obesity, identified only 12 studies with few and weak associations, found no evidence for a consistent association and found no qualitative studies examining SB associations in this population. 14 Furthermore, while qualitative studies have focused on perceived determinants of weight loss, 15 obesity management, 16 physical activity, 17 healthy lifestyle or nutrition 18 in adults with obesity or adolescents, 19 few use a theoretical framework from study design through analysis. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%